Conserving health in early modern culture : bodies and environments in Italy and England - Astbury, Leah; Newton, Hannah (Social histories of medicine., 2017)
Conserving Health brings together scholarship from across the disciplinary spectrum to illustrate the role of preventive culture in early modern England and Italy, its ubiquity but also how patterns of healthy living differed in different countries.